Relationship between the number of brushings per day and periodontal self-perception in 12-year-old school children from Ecuador - Castro-Cabrera, Suley Elizabeth (2021)
Objective: To determine the number of brushings per day and periodontal self-perception in 12-year-old schoolchildren from the Machángara parish, in Cuenca Ecuador in 2016. Materials and methods: A descriptive, retrospective, relational level study was conducted. The sample consisted of 205 records of 12-year-old schoolchildren residing in the Machángara parish, which belongs to the epidemiological map of oral health in Cuenca, performed by the Catholic University of Cuenca. For analysis of the data, descriptive statistics were used with frequencies and percentages for each of the variables and the Kendall Tau-b statistical test was performed to determine the correlation between the main variables of the study, according to a significance of 0.05. Results: 50.7% of adolescents were male, 49.3% female, and 94.1% were in public schools. It was found that 50.2% of the study population brushed three times a day, being 51.5% among females and 48.1% among males. The prevalence of periodontal self- perception was 85.4%: 86.1% in girls and 84.6% in boys. An inverse and significant negative correlation was found between the number of brushings per day and periodontal self-perception (Tau-b: -0.178; p: 0.004). Brushing frequency had an inverse and significant negative correlation with periodontal self-reporting for females (tau-b: -0.197; p value: 0.030) and a non-significant correlation for males.  Conclusion: There is an inverse and significant negative correlation between the frequency of daily brushing and periodontal self-perception. Educational strategies regarding oral health are needed for adolescents from the Machángara parish of Cuenca.